2023
DOI: 10.1186/s12876-023-02826-z
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative balance score and dietary phytochemical index can reduce the risk of colorectal cancer in Iranian population

Shahrooz Bentyaghoob,
Fereshteh Dehghani,
Arezoo Alimohammadi
et al.

Abstract: Background No previous study has assessed the association between oxidative balance score (OBS) and dietary phytochemical index (DPI) with colorectal cancer (CRC) simultaneously. Therefore, this study investigated the association between OBS and DPI with the odds of CRC among the Iranian population. Methods This hospital-based age and sex-matched case–control study was conducted between September 2008 and January 2010 (142 controls and 71 cases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Higher OBS obtained by summation was positively associated with total antioxidant capacity in participants. On the basis of previous studies, 29,30 we grouped the OBS into tertiles and defined the first tertile of the OBS as OBS Q1 (range: scores 3 to 16) and its second and third tertiles as OBS Q2 (range: scores 17 to 23) and OBS Q3 (range: scores 24 to 35), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Higher OBS obtained by summation was positively associated with total antioxidant capacity in participants. On the basis of previous studies, 29,30 we grouped the OBS into tertiles and defined the first tertile of the OBS as OBS Q1 (range: scores 3 to 16) and its second and third tertiles as OBS Q2 (range: scores 17 to 23) and OBS Q3 (range: scores 24 to 35), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…All subjects were required to provide written informed consent before the interview. Details of the current study have been previously published [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The OBS was first proposed in 2002 in an epidemiologic study of a Belgian male smoking population, which used vitamin C and β-carotene as the antioxidant constituents and iron as the pro-oxidant constituent and showed that the lower the OBS score was, the higher the level of oxidative homeostasis in an individual, indicating that the lower the oxidative homeostasis score was, the higher the mortality rate in the population (15). Thereafter, numerous studies were conducted to investigate the relationship between OBS and a wide range of chronic disorders, such as type 2 diabetes mellitus (16), cardiovascular disease (17), and colorectal cancer (18). Recently, a study conducted in Iran showed that the greater the adherence to an OBS, the lower the odds of developing NAFLD (19).…”
Section: Introductionmentioning
confidence: 99%